Incidence and spatial distribution of lymphatic filariasis in Sarawak, 2018-2022 - Ariffin, Mohd Aslam (2023)
Introduction: Lymphatic filariasis is a neglected tropical disease caused by Wuchereria bancrofti, Brugia malayi, or Brugia timori. It leads to severe morbidity and have a significant impact on health. Spatial analysis helps identify hotspot areas in Sarawak, enabling better targeting and focusing of prevention and control activities. Objective: To investigate the incidence and geographic dispersion of lymphatic filariasis in the region of Sarawak during the period ranging from 2018 to 2022, identify spatial distribution and hotspot area with present of any autocorrelation between cases. Methodology: This study utilized secondary data from Vekpro online system, Sarawak State Health Department for all cases registered from period of 2018 till 2022. The data pertaining to the population of Sarawak were acquired from the Department of Statistics Malaysia. The coordinates were transformed into the format of Kertau Rectified Skewed Orthomorphic (RSO) Malaya (EPSG:3168). The incidence of filariasis was calculated at the district level, and point pattern analysis was conducted using Kernel Density Estimates and Nearest Neighboring Index (NNI). The study additionally examines the existence of hot spots in order to differentiate spatial risk at the district level. Analyses were done using the gtsummary, tmap, spdep, spatialeco, and spastat packages in R Software Version 4.2.3. Result: There were varying incidence rates, with the highest in 2018 at 4.7 cases per 100,000 population followed by fluctuation trend, which 0.4 cases per 100,000, 2.3 cases per 100,000, 0.9 cases per 100,000 and 2.7 cases per 100,000 population in 2019, 2020, 2021 and 2022 respectively. The kernel density estimator (KDE) showed the potential hotspot area in the northern region of Sarawak, mainly Limbang district. The nearest neighbouring index (NNI) showed there was statistically significant clustering of filariasis cases, but using Global Moran’s I analysis, it showed there was no spatial autocorrelation between adjacent districts where confirmed filariasis was registered in Vekpro online system. Conclusion: The implementation of mass drug administration (MDA) has resulted in a reduction in filariasis infections in Sarawak. However, it is important to note that the risk of filariasis remains significantly high, particularly in the northern region. The application of spatial statistics and cluster detection techniques assists health planners in accurately evaluating and detecting spatial inequalities in risk among populations. Cluster analysis aids in the identification and prioritisation of regions with persistent transmission, preventing the spread of infection and subsequent resurgence on a larger scale.